Athletes sleep duration during COVID-19 pandemic and its relationship with health condition - Jull Kurniarobbi; Chikih Chikih; Muhammad Andeansah; Ria Lestari; Irfan Sukendar (Intelektual Pustaka Media Utama, 2022)
During the coronavirus desease 2019 (COVID-19) pandemic, athletes must be able to adapt to new habits, such as: social restriction, change of competition schedule, and sending back home. This situation has led to an 18.2% increase in sleep disturbances. This study aimed to look at the sleep duration of adolescent athletes during the COVID-19 pandemic and its impact on athlete’s health conditions. A total of 126 adolescent athletes from 15 sports were recruited in this cross-sectional study. Adequate sleep duration was assessed according to the American Academy of Sleep Medicine criteria. Data on health conditions, medical history, injury history, were taken using a questionnaire. Behavioral assessment was assessed through the strengths and difficulties questionnaire. About 80.2% of adolescent athletes had insufficient sleep, and there was a significant relationship between sleep duration and disease incidence with a relative risk (RR) of 3.31 (1.32-8.28) 95% convidence interval (CI). There was no significant relationship between adequate sleep duration and health conditions (p>0.05). Things that may be the cause of sleep disturbances; use of electronic devices (37.6%), environmental conditions (53.4%), and worry (9%). In the end, this indicates adolescent athletes face difficulties in achieving adequate sleep duration during this pandemic and a continuous surveillance system is needed to monitor athletes outside the dormitory.